Strategi Pengelolaan Konten Media Sosial Instagram pada Dinas Pariwisata dan Kebudayaan Majalengka - Kistia Rindika; Rini Rinawati (Bandung Conference Series: Communication Management, 2023)
The activities carried out by the Majalengka Tourism and Culture Office @disparbudmajelengka and followers tend to be more from the Instagram accounts @disparbudpnd (Pangandaran Tourism and Culture Office), @disparbudbekasi (Bekasi Tourism and Culture Office), and there are 40 more tourism office accounts and other cultures, of course, cannot be avoided from the Instagram social media content management strategy. Because in practice it is certainly not arbitrary for government social media accounts to manage their content and it is not easy to maintain their existence. Because it turns out that it is not easy to do this if you look at the existing data regarding the number of tourism and culture service accounts in other regions that are not yet like the Majalengka Tourism and Culture Office. The object of this research is the Instagram Department of Tourism and Culture Majalengka @disparbudmajalengka. This study aims to determine the planning of content management by the Department of Tourism and Culture Majalengka on Instagram @disparbudmajalengka. This study uses a qualitative method with a case study approach. Planning in content management carried out by the Majalengka Tourism and Culture Office is through several stages ranging from planning, implementation, data analysis, content drafts, content discussions, decisions, and uploads. The implementation in content management carried out by the Majalengka Tourism and Culture Office is scheduled and themed. The goal in content management carried out by the Majalengka Tourism and Culture Office is to get a broad market segmentation.